2020
DOI: 10.1111/apa.15598
|View full text |Cite
|
Sign up to set email alerts
|

Birth weight increases with birth order despite decreasing maternal pregnancy weight gain

Abstract: Aim We investigated whether birth order is an influencing factor for birth weight independent from maternal factors. Methods Data were obtained from the longitudinal cohort study LIFE Child and included 1864 children, of which 526 were only children. The 1338 siblings were ranked into first‐borns (n = 570), second‐borns (n = 606) and third‐or‐later‐borns (n = 162). Children born prematurely, suffering from chronic or syndromic diseases, were excluded. We performed intra‐family comparisons to reduce bias and as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 29 publications
1
17
0
3
Order By: Relevance
“…Mothers of first-born children had the lowest prepregnancy BMI ( Table 2 ). As previously shown [ 25 ], maternal pregnancy weight gain was significantly lower (p<0.001) with increasing birth order. The prepregnancy BMI of mothers of only children, second- and third-or-later-born children was comparable.…”
Section: Resultssupporting
confidence: 84%
“…Mothers of first-born children had the lowest prepregnancy BMI ( Table 2 ). As previously shown [ 25 ], maternal pregnancy weight gain was significantly lower (p<0.001) with increasing birth order. The prepregnancy BMI of mothers of only children, second- and third-or-later-born children was comparable.…”
Section: Resultssupporting
confidence: 84%
“…A German study of 1,338 siblings showed that birthweight increased with birth order, despite decreasing maternal weight gain during pregnancy. 1 Bohn et al conclude that birth order must be considered a potential risk factor for higher birth weight. Hermanussen comments on the findings.…”
Section: Bir Thweight Increased With Bir Th Order Despite Decreasingmentioning
confidence: 99%
“…Bohn et al 1 aimed to investigate whether the birth order had an essential function in the development of different BW of siblings. BW does increase with birth order.…”
Section: Changes Of Uterine Size After Pregnancymentioning
confidence: 99%
“…Finally, Bohn et al 1 concluded that “birth order must be considered a potential risk factor for higher BW, and that maternal pregnancy weight gain is not the driving factor for higher BW in siblings”.…”
Section: Changes Of Uterine Size After Pregnancymentioning
confidence: 99%
See 1 more Smart Citation